Heat/mass transfer and fluid friction irreversibility aspects in peristalsis of physiological material using ellis model between slippery asymmetric configuration - Faisal Shah; Shahid Farooq; Khurram Shahzad; Ehab Ghith; Muhammad Waqas; Dalal A. Alshammari; Mohamed Kallel (Case Studies in Thermal Engineering)
Peristaltic movement of Ellis liquid with entropy effects through asymmetric propagating channel waves is discussed in this attempt. Slip effects of momentum, thermal and concentration are taken at channel walls. Transfer of heat and mass phenomenons are examined by considering the effects of viscous dissipation, chemical reaction and Soret. Entropy generation is discussed in the presence of irreversibilities due to fluid friction and heat and mass transfer. Flow equations are modeled using fixed frame of reference and then simplified these equations via long wave length and low Reynolds approximations. Here solution for the system of simplified equations are obtained in terms of series for small material parameter. With the help of obtained solutions flow quantities behavior is plotted against sundry dimensionless quantities.